Characteristics of food allergy in children: National multicenter study - Bingol, A.; Uygun, Kocacik D. F.; Akdemir, M.; Erengin, H.; Bozdogan, G.; Bingol, G.; Altintas, Ufuk D. (Wiley, 2019)
[Abstract Not Available]
Congress of the European-Academy-of-Allergy-and-Clinical-Immunology (EAACI) -- JUN 01-05, 2019 -- Lisbon, PORTUGAL